2009
DOI: 10.2967/jnumed.108.059360
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous PET Imaging of P-Glycoprotein Inhibition in Multiple Tissues in the Pregnant Nonhuman Primate

Abstract: Studies in rodents indicate that the disruption of P-glycoprotein (P-gp) function increases drug distribution into the developing fetus and organs such as the brain. To simultaneously and serially evaluate the effect of P-gp activity and inhibition on the tissue distribution of drugs in a more representative animal model, we tested the feasibility of conducting whole-body PET of the pregnant nonhuman primate (Macaca nemestrina). We used 11 C-verapamil as the prototypic P-gp substrate and cyclosporine A (CsA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…Likewise, fetal penetration of the cardiac glycoside digoxin, the antiviral drug saquinavir, and the chemotherapeutic agent paclitaxel is enhanced in Mdr1a/1b-null mice (Smit et al, 1999). Similar to knockout mice, when pregnant macaques are administered the Pgp inhibitor cyclosporine A, the penetration of radiolabeled verapamil (Pgp substrate) into maternal brain and fetal livers increases (Eyal et al, 2009). Active efflux of potentially toxic chemicals from the fetus to the mother via Pgp may represent a protective mechanism to limit drug-induced birth defects.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Likewise, fetal penetration of the cardiac glycoside digoxin, the antiviral drug saquinavir, and the chemotherapeutic agent paclitaxel is enhanced in Mdr1a/1b-null mice (Smit et al, 1999). Similar to knockout mice, when pregnant macaques are administered the Pgp inhibitor cyclosporine A, the penetration of radiolabeled verapamil (Pgp substrate) into maternal brain and fetal livers increases (Eyal et al, 2009). Active efflux of potentially toxic chemicals from the fetus to the mother via Pgp may represent a protective mechanism to limit drug-induced birth defects.…”
mentioning
confidence: 92%
“…Using positron emission tomography, it has been shown that administration of the Pgp inhibitor cyclosporine A to pregnant macaques increases the penetration of radiolabeled verapamil (Pgp substrate) into brain (Eyal et al, 2009). This imaging modality may be important in screening chemicals for Mdr1a/1b inhibition.…”
Section: Efflux Transporters In Brainmentioning
confidence: 99%
“…Similarly, as previously demonstrated by us and others (Sasongko et al, 2005;Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Bauer et al, 2012;Mullauer et al, 2012;Bankstahl et al, 2013;Ke et al, 2013;Deo et al, 2014), when a drug is effluxed out of the brain, its concentration in the brain can be much lower than that in the plasma. This disconnect between tissue and plasma drug concentration will be modulated in the presence of a drug-drug interaction (DDI).…”
Section: Quantification Of Drug Transporters To Understand Interindivmentioning
confidence: 49%
“…Such data are best obtained using noninvasive imaging methods (such as PET imaging) to determine drug transport concentrations in various tissues (e.g., brain, fetus, and liver). Such data are available from our laboratory (Hsiao et al, 2008;Eyal et al, 2009Eyal et al, , 2010Muzi et al, 2009;Ke et al, 2013;Deo et al, 2014;He et al, 2014) and others. Therefore, the accuracy of the above proposed IVIVE method can now be tested.…”
Section: Quantification Of Drug Transporters To Understand Interindivmentioning
confidence: 99%
“…11 C]-verapamil (29,36,69,70) and its (R)-enantiomer (39,(71)(72)(73) and the radiolabeled loperamide metabolite, [ 11 C]-dLop (48,74). In addition to these compounds, cytotoxic drugs, such as daunorubicin (43) and paclitaxel (75), have been radiolabelled and evaluated in various tumor models in rodents (Table III).…”
Section: Petmentioning
confidence: 99%